Is Type 2 diabetes mellitus associated with an increased pathological burden in clinically and pathologically diagnosed Alzheimer's dementia?: Human neuropathology/clinico‐pathologic correlations. (7th December 2020) - Sadrolashrafi, Kaviyon; Miller, Justin B.; Decourt, Boris; Adem, Abdu; Sabbagh, Marwan N.
Abstract: Background: Epidemiological evidence suggests that Alzheimer's disease (AD) and Type‐2 Diabetes Mellitus (T2DM) share pathophysiological processes. T2DM causes central insulin resistance, which generates a hypoglycemic microenvironment in the brain. The oxidative stress established as a result leads to mitochondrial dysfunction, inflammation, advanced glycation end‐product (AGE) production, insulin receptor signaling pathway impairment, and insulin‐degrading enzyme (IDE) inhibition. These widespread repercussions catalyze amyloid‐β (Aβ) plaque and neurofibrillary tangle (NFT) formation. Here, we hypothesize that T2DM is associated with an increased AD pathological burden in clinically‐ and pathologically‐diagnosed AD. Method: All data were obtained from the Uniform Data Set (UDS) v3, the Neuropathology Data Set, and the Researcher's Data Dictionary‐Genetic Data from the NIA funded National Alzheimer's Coordinating Center (NACC). The data was compiled by NACC in a dataset querying, the following keywords: "Alzheimer's disease", "Type 2 diabetes mellitus", "Thal phase (A score)", "Braak neurofibrillary stage (B score)", "Neuritic plaque score (C score)", and "Alzheimer's disease neuropathology change (ABC score)". The dataset relies on autopsy‐confirmed data in clinically‐diagnosed AD patients who were assessed for diabetes type in form A5 or D2 during at least one visit. In our analysis, there were 271 AD cases with T2DM and 8, 431 cases without. Differences in scores were explored using one‐way ANOVA. Effect sizes were calculated using sample means and standard deviations (Cohen's d ). Result: The differences in pathology staging between AD‐confirmed individuals with T2DM and those without were statistically significant, with effects ranging from medium ( d  = ‐0.34; r  = ‐0.17) to large ( d  = 0.53 and 0.51; r  = 0.25). The presence of recent or active T2DM was associated with a higher Thal phase of amyloid plaques (μdiff = 1.89) as well as a higher NIA‐AA Alzheimer's disease neuropathologic change, ADNC (μdiff = 1.57). The presence of T2DM was also correlated to a lower Braak stage for neurofibrillary degeneration (μdiff = ‐0.30). Conclusion: These findings suggest that there is more amyloid burden in individuals with AD and T2DM than AD without T2DM. Our results indicate that individuals with T2DM have significantly higher amounts of plaques by Thal stage, as well as higher ABC scores.